The Impact of Unexpected Maternal Death on Education: First Evidence from Three National Administrative Data Links - Chen, Stacey H; Chen, Yen-Chien; Liu, Jin-Tan (American Economic Review, 2009)
The Impact of Unexpected Maternal Death on Education: First Evidence from Three National Administrative Data Links by Stacey H. Chen, Yen-Chien Chen and Jin-Tan Liu. Published in volume 99, issue 2, pages 149-53 of American Economic Review, May 2009